New control strategy for the weekly scheduling of insular power systems with a battery energy storage system. (15th September 2015) - Osório, G.J.; Rodrigues, E.M.G.; Lujano-Rojas, J.M.; Matias, J.C.O.; Catalão, J.P.S.
Highlights: A new control strategy is presented for the day-ahead scheduling of insular power systems. The method presented here incorporates the effects of the most relevant components. Thermal generators, wind power generation, power converter, charge controller and ESS are integrated. The results provided show a fuel saving of 2% and an improvement in the wind power use of 20%. Abstract: The increment in generation costs is one of the most important factors that characterizes the operation of insular power systems, and is related to the location of these systems and the type of fuel used to provide electricity. This situation motivates the integration of renewable generation at high rates, as well as energy storage systems (ESSs), to improve the utilization of these resources. In this paper, a new control strategy is presented for the day-ahead scheduling of insular power systems with a battery energy storage system. The method presented here incorporates the effects of the most relevant components such as thermal generators, wind power generation, power converter, charge controller and ESS, being integrated into the scheduling process of insular power systems as a new contribution to earlier studies. The results provided show a fuel saving of 2% and an improvement in the wind power use of 20%, which is significant.